Non-coding RNAs: emerging biomarkers and therapeutic targets in cancer and inflammatory diseases - Hossam Abdelmonem, Basma; Kamal, Lereen T.; Wardy, Lilian Waheed; Ragheb, Manon; Hanna, Mireille M.; Elsharkawy, Mohamed; Abdelnaser, Anwar (Frontiers in Oncology, 2025)
Non-coding RNAs (ncRNAs) have a significant role in gene regulation, especially in cancer and inflammatory diseases. ncRNAs, such as microRNA, long non-coding RNAs, and circular RNAs, alter the transcriptional, post-transcriptional, and epigenetic gene expression levels. These molecules act as biomarkers and possible therapeutic targets because aberrant ncRNA expression has been directly connected to tumor progression, metastasis, and response to therapy in cancer research. ncRNAs’ interactions with multiple cellular pathways, including MAPK, Wnt, and PI3K/AKT/mTOR, impact cellular processes like proliferation, apoptosis, and immune responses. The potential of RNA-based therapeutics, such as anti-microRNA and microRNA mimics, to restore normal gene expression is being actively studied. Additionally, the tissue-specific expression patterns of ncRNAs offer unique opportunities for targeted therapy. Specificity, stability, and immune responses are obstacles to the therapeutic use of ncRNAs; however, novel strategies, such as modified oligonucleotides and targeted delivery systems, are being developed. ncRNA profiling may result in more individualized and successful treatments as precision medicine advances, improving patient outcomes and creating early diagnosis and monitoring opportunities. The current review aims to investigate the roles of ncRNAs as potential biomarkers and therapeutic targets in cancer and inflammatory diseases, focusing on their mechanisms in gene regulation and their implications for non-invasive diagnostics and targeted therapies. A comprehensive literature review was conducted using PubMed and Google Scholar, focusing on research published between 2014 and 2025. Studies were selected based on rigorous inclusion criteria, including peer-reviewed status and relevance to ncRNA roles in cancer and inflammatory diseases. Non-English, non-peer-reviewed, and inconclusive studies were excluded. This approach ensures that the findings presented are based on high-quality and relevant sources.